Ferroelastic property of tetramethylammonium tetrachlorozincate tetrachlorocuprate, [N(CH3)4]2Zn1−xCuxCl4 (x = 0, 0.1, 0.3, 0.5, and 1). Issue 35 (16th March 2015) - Lim, Ae Ran
Abstract : The various crystallographic structures of [N(CH3 )4 ]2 Zn1− x Cu x Cl4 ( x = 0, 0.1, 0.3, 0.5, and 1) may be understood by considering the different chemical shifts observed in 1 H MAS and 13 C CP/MAS NMR spectra. Abstract : The various crystallographic structures of [N(CH3 )4 ]2 Zn1− x Cu x Cl4 ( x = 0, 0.1, 0.3, 0.5, and 1) may be understood by considering the different chemical shifts observed in 1 H MAS and 13 C CP/MAS NMR spectra. Cu 2+ ions, after replacing partially the Zn 2+ ions, occupy the same locations in the lattice as the Zn 2+ ions. The NMR spectrum and T 1ρ of x = 0.1 and 0.3 were found to be similar to those of pure [N(CH3 )4 ]2 ZnCl4, whereas the NMR spectrum and T 1ρ of x = 0.5 were different. Consequently, the existence of ferroelastic properties of N(CH3 )4 ions in x = 0, 0.1, 0.3, and 1 are apparent at low temperatures, whereas they disappear for x = 0.5. It has been demonstrated that the replacement of Zn 2+ ions with high concentrations of Cu 2+ ions changes the ferroelastic property of the crystal.